Examining the effects of demographic factors on open school learners’ academic performance in Dar es Salaam region, Tanzania - Ibengwe, Tukumbukege; William, Yohana (Papers in Education and Development, 2024)
Open schools in Tanzania aim to expand access to secondary education for learners who may be out of school for various reasons, offering a second chance and addressing deficiencies in formal secondary education that are not accessible to everyone due to admission criteria. Despite this, there is a significant disparity in academic performance among learners in Open schools. This paper examines the potential effect of demographic factors: age, educational level, and occupation, on the academic performance of these learners. The study employed a quantitative research approach with a cross-section-survey design to collect data from a sample of 30 Open schools and 454 learners. The results showed that demographic factors among learners in Open schools do not have a discernible effect on their academic performance. These findings suggest that demographic characteristics do not serve as the determinants of the learners’ academic performance in Open schools.